The impact of Covid-19 pandemic on transportation - the rail transportation company as a case study- - مخلوفي مريم; حاجي اسحاق زكرياء (المجلة الجزائرية للأمن والتنمية Algerian Review of Security and Developement, 2023)
This paper analyses how the transportation is impacted because of the policies adopted by the Algerian government for the containment of the COVID-19. Various official sources of data such as website, Google mobility trends, were consulted along with recently published research articles on COVID-19 and its impacts. The secondary sources of data the relationship between COVID-19 prevention measures and the transportation, and the rail transportation company of Algeria as a case study. The results of this study showed reduced demand for transporation with the adoption of COVID-19 prevention measures. Declines in revenues in the transport industry. The survey shows that transportation in Algeria is facing a serious financial downfall has dropped by 70%, a 62,7% drop in revenues. The recovery of the transport sector to the pre-pandemic state is only possible with the relaxation of COVID-19 containment policies and financial support by the government.